Association between frontal fibrosing Alopecia and Rosacea: Results from clinical observational studies and gene expression profiles - Liu, Lin; Chen, Yangmei; Chen, Jiayi; Xue, Yuzhou; Chen, Tingqiao; Li, Yuxin; Shao, Xinyi; Chen, Jin (Frontiers in Immunology, 2022)
Background: In recent years, frontal fibrosing alopecia (FFA), a type of scarring alopecia, has attracted increasing attention. Several studies have reported the frequent occurrence of rosacea in FFA; however, the association between FFA and rosacea and the underlying pathogenesis have not been thoroughly clarified. Thus, this study aimed to quantify these relationships and investigate their shared molecular mechanisms. Methods: We evaluated the association between FFA and rosacea by analyzing clinical data from nine observational studies. We then analyzed the gene expression profiles of FFA and rosacea. First, differential expression analysis and weighted gene co-expression network analysis were used to identify the common differentially expressed genes (DEGs). Later, we conducted a functional enrichment analysis and protein-protein interaction network and used seven algorithms to identify hub genes. Then, we performed a correlation analysis between the hub genes and the gene set variation analysis scores of common pathways in the gene set enrichment analysis (GSEA). The results were validated using different datasets. Finally, transcription factors were predicted and verified, and CIBERSORT and single-sample GSEA were used to estimate the infiltrating immune cells. Results: Patients with FFA had significantly higher odds for rosacea (pooled odds ratio [OR], 2.46; 95% confidence interval [CI], 1.78–3.40), and the pooled prevalence of rosacea in patients with FFA was 23% (95% CI, 14–23%). Furthermore, we identified 115 co-DEGs and 13 hub genes (CCR5, CCL19, CD2, CD38, CD83, CXCL8, CXCL9, CXCL10, CXCL11, CXCR4, IRF1, IRF8, and PTPRC). Seven pathways showed a high correlation with these hub genes. In addition, one TF, STAT1, was highly expressed in both diseases, and the results of the immune infiltration analysis indicated the importance of M1 macrophages and effector memory CD8+ T cells. Conclusion: This study contributes to the understanding of the relationship between FFA and rosacea, and based on the hub genes, we reveal the potential pathologies shared by the two diseases. This finding provides new insights of underlying molecular mechanisms and it may inspire future research on this comorbidity.